MICRO-CREDENTIALS IN HIGHER EDUCATION: MAPPING AND NETWORKING DATA USING BIBLIOMETRIC ANALYSIS - Nanah Sujanah; Sholeh Hidayat; Fadlullah Fadlullah (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
Micro-credentials have become an important innovation in higher education due to growing demands for flexible, competency-based, and industry-oriented learning systems. Digital transformation, workforce disruption, and lifelong learning needs have increased scholarly attention toward micro-credentials as alternative pathways for skills development and employability enhancement. This study aims to map publication trends, intellectual structures, dominant themes, and emerging research directions related to micro-credentials in higher education. A bibliometric approach was employed using Scopus-indexed publications analyzed through science mapping, co-occurrence analysis, Bradford’s Law, and network visualization techniques. The findings show that research on micro-credentials has grown significantly after 2020, particularly in themes related to digital credentials, employability, lifelong learning, workforce development, online learning, and educational technology. The United States emerged as the most productive country, while technology-oriented journals and universities dominated the publication landscape. The analysis also identified emerging topics such as blockchain integration, personalized learning, quality assurance, and artificial intelligence as promising directions for future research. Overall, the study demonstrates that micro-credentials have evolved into a rapidly growing interdisciplinary field that plays an increasingly strategic role in higher education transformation, digital learning ecosystems, and workforce adaptability.